Chitosan as an Immunomodulating Adjuvant on T-Cells and Antigen-Presenting Cells in Herpes Simplex Virus Type 1 Infection. (21st December 2016) - Choi, Bunsoon; Jo, Do-Hyun; Anower, A. K. M. Mostafa; Islam, S. M. Shamsul; Sohn, Seonghyang
Abstract : Herpes disease caused by herpes simplex virus type 1 (HSV-1) is an intractable condition. It is a major concern in public health. Our purpose of this study was to verify the function of chitosan as an adjuvant for immune regulation specifically under herpes simplex virus type 1 (HSV-1) infection. Ahead of HSV infection, chitosan, heat inactivated green fluorescent protein expressing HSV (G-HSV), and a combination of chitosan and G-HSV were used to pretreat ICR mice followed by HSV-1 infection. Using flow cytometric analysis, the frequencies of T-cells, monocytes, dendritic cells (DCs), and natural killer (NK) cells were analyzed by surface expression ofC D 4 +, C D 8 +, C D 14 +, C D 11 c +, N K 1.1 +, andD X 5 + cells. In HSV infected mice, chitosan treatment significantly increased the frequencies ofC D 4 + T-cells (33.6 ± 5.78 %) compared to those in the control group (24.02 ± 12.47 %, p = 0.05 ). The frequencies of DC and NK cells were also significantly different between chitosan treated mice and control mice. In addition, anti-HSV IgG antibody was downregulated in chitosan treated mice. These results suggest that chitosan is a potential modulator or immune stimulator as an adjuvant in HSV-1 infected mice.